2014
DOI: 10.1103/physrevb.89.180101
|View full text |Cite
|
Sign up to set email alerts
|

Positional disorder in ammonia borane at ambient conditions

Abstract: We solve a long-standing experimental discrepancy of NH 3 BH 3 , which-as a molecule-has a threefold rotational axis, but in its crystallized form at room temperature shows a fourfold symmetry around the same axis, creating a geometric incompatibility. To explain this peculiar experimental result, we study the dynamics of this system with ab initio Car-Parrinello molecular dynamics and nudged-elastic band simulations. We find that rotations, rather than spatial static disorder, at angular velocities of 2 rev/p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…tentials,G aussian basis-sets, all-electron augmented plane waves). [75] Recently,t he calculated values fort he equationo fs tates were compared using 40 different DFTm ethodt ypes showing that deviations between the accurate codes are smaller than those of experiments.…”
Section: Theoretical Quantum Crystallographymentioning
confidence: 99%
See 1 more Smart Citation
“…tentials,G aussian basis-sets, all-electron augmented plane waves). [75] Recently,t he calculated values fort he equationo fs tates were compared using 40 different DFTm ethodt ypes showing that deviations between the accurate codes are smaller than those of experiments.…”
Section: Theoretical Quantum Crystallographymentioning
confidence: 99%
“…[74] As af urthere xample, the usage of modernn on-local functionals coupled with molecular dynamics has allowed to interpret experimental resultsi nm olecular crystalsa tf inite temperature. [75]…”
Section: Theoretical Quantum Crystallographymentioning
confidence: 99%
“…The additional height of these barriers is due to disruption of the material's dihydrogen bond network, which is much more rigid in the low-temperature phase we are using for our simulations. In a previous study, 39 we found that signicant barriers to disrupting this network (by rotating molecules, for instance) do not exist in the roomtemperature phase of pure AB, where the desorption reaction occurs experimentally. However, the most striking result in Table 7 is that the kinetic barriers for H 2 desorption in the Cu-substituted material are signicantly lower than those of pure AB.…”
Section: H 2 Release Barriers In the Bulkmentioning
confidence: 78%
“…The RDFs discussed above are averaged over orientational degrees of freedom and, therefore, cannot directly quantify orientational order in the acetylene:ammonia (1:1) co-crystal. To quantify the orientational structure of ammonia molecules within the co-crystal, we compute the probability distribution of ammonia H atom positions projected on the xz plane of the crystal . At 30 K, the ammonia molecules are orientationally ordered, as reflected by the distinct, disconnected regions of high probability, Figure a.…”
Section: Resultsmentioning
confidence: 99%